2022
DOI: 10.1002/adfm.202211009
|View full text |Cite
|
Sign up to set email alerts
|

All‐Visible‐Light Triggered Photoswitch of Dithienylethene Derivatives with Molecular Conformation Changes Excess 5 Å

Abstract: Developing new all‐visible‐light driven fluorescent molecular switches has attracted much interests due to their important application prospects in materials science and life science. Herein, three novel all‐visible‐light triggered fluorescent molecular photoswitches (2P3, 4F, and 4Cl) are designed and prepared, which are realized by prolonging π‐conjugation length with aggregated‐induced emission units. These photoswitches show reversible photochromic and fluorescent switching in dilute solutions and films un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…In addition, it was found that the compounds connected with tetraphenylethene and BTE showed brighter emission than those with triphenylethene and BTE in the solid state. In addition, Luo et al 136 synthesized three fluorescent molecular optical switches with similar structures by extending the π conjugate length of the aggregation-induced emission units. These optical switches showed two different conformations in different polar solvents, resulting in different photochromic behaviours, which are used for visible-light manipulated data storage and anti-counterfeiting.…”
Section: Solid-state Small-molecule Fluorescent Photoswitchesmentioning
confidence: 99%
“…In addition, it was found that the compounds connected with tetraphenylethene and BTE showed brighter emission than those with triphenylethene and BTE in the solid state. In addition, Luo et al 136 synthesized three fluorescent molecular optical switches with similar structures by extending the π conjugate length of the aggregation-induced emission units. These optical switches showed two different conformations in different polar solvents, resulting in different photochromic behaviours, which are used for visible-light manipulated data storage and anti-counterfeiting.…”
Section: Solid-state Small-molecule Fluorescent Photoswitchesmentioning
confidence: 99%
“…In essence, a highly efficient visible light system usually rely on constructing a conjugated molecule system no matter it is triplet energy transfer, intramolecular proton transfer, or nonlinear optics. In comparison, the simpler and more direct approach to visible light responsibility is to extend the π‐conjugation length of the molecule to shift the absorption wavelength into the visible light region [9d,18] . However, this approach frequently doesn't work, as an conjugation‐extended diarylethene system commonly results in reduce of the photochromic efficiency and even the photoswitching capacity [19] .…”
Section: Introductionmentioning
confidence: 99%
“…14 Reported instances of organic photochromic materials showcase a myriad of color change mechanisms, such as intermolecular electron transfer, 15 constitutional transformations, 16 and conformational changes. 17 Despite the significant progress made so far in this field, the development of multifunctional photochromic dyes with high contrast, reversibility, and scalability, which are fundamental features for smart textile applications, remains a challenge.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Notably, organic photochromic colorants are especially suited for textile applications, primarily owing to their diverse color range, cost-effectiveness, and versatility in terms of structure and properties . Reported instances of organic photochromic materials showcase a myriad of color change mechanisms, such as intermolecular electron transfer, constitutional transformations, and conformational changes . Despite the significant progress made so far in this field, the development of multifunctional photochromic dyes with high contrast, reversibility, and scalability, which are fundamental features for smart textile applications, remains a challenge.…”
Section: Introductionmentioning
confidence: 99%